PENINGKATAN KUALITAS PEMBELAJARAN IPS MENGGUNAKAN SNOWBALL THROWING MEDIA AUDIO VISUAL KELAS IV (Universitas Negeri Semarang, 2013)
Tujuan umum penelitian ini: meningkatkan kualitas pembelajaran IPS menggunakan model Snowball Throwing dengan media Audio Visual. Tujuan khusus penelitian ini: meningkatkan keterampilan guru, aktivitas siswa dan hasil belajar siswa dalam pembelajaran IPS menggunakan model Snowball Throwing dengan media Audio Visual. Penelitian Tindakan Kelas ini dilaksanakan sebanyak 2 siklus. Subyek penelitian ini adalah guru dan siswa kelas IVA. Hasil penelitian ini adalah model Snowball Throwing dengan media Audio Visual dapat meningkatkan kualitas pembelajaran IPS siswa kelas IVA. Simpulan penelitian ini yaitu model Snowball Throwing dengan media Audio Visual dapat meningkatkan kualitas pembelajaran IPS yang meliputi keterampilan guru,aktivitas siswa dan hasil belajar siswa kelas IVA. Saran peneliti sebaiknya guru menerapkan model Snowball Throwing dengan media Audio Visual dalam kegiatan pembelajaran. The general objective of this research: improve the quality of teaching social studies using models of Snowball Throwing with Audio Visual media. The specific aims of this research: improve the skills of teachers, student activities and student learning in social studies using models of Snowball Throwing with Audio Visual media. Classroom Action Research was conducted by 2 cycles. The subjects of this research were teacher and student IVA classroom.The result of this research is Snowball Throwing model’s with Audio Visual media’s can improve the quality of social studies IVA classroom. Conclusions of this research is the models of Snowball Throwing with Audio Visual media can improve the quality of social studies teachers that includes teacher’s skills, student activities and student learning in IVA class. Researchers suggest is teachers should apply the models of Snowball Throwing with Audio Visual media in learning activities.